Effects of daily porcine somatotropin administration on the performance and carcass characteristics of finishing swine - G E Fitzner; David A Nichols; B R Schricker; D E Darden; T L Weeden; Robert D Goodband; Robert H Hines; Jim L Nelssen; Donald H Kropf (Kansas Agricultural Experiment Station Research Reports, 1989)
One hundred forty-four pigs (72 barrows and 72 gilts) were utilized in six treatments with six pens each to evaluate four levels of daily porcine somatotropin (pST) injections (0, 1, 3, or 5 mg/d) in combination with diets containing 13 or 16% crude protein (CP). One randomly selected pig from each pen was slaughtered when it reached a weight between 230 and 240 lb. Daily feed intake (ADFI), tenth rib backfat, and estimated percentage of lean pork were reduced in pigs fed the 13% CP diet and injected with 3 mg/d pST compared to pigs fed the same diet and injected daily with a placebo. Feed intake was reduced in pigs fed the 16% CP diet and injected daily with 3 and 5 mg/d pST. Improvement in feed conversion (F/G), tenth rib backfat, and estimated percentage lean pork occurred when pigs fed the 16% CP diet were injected with 1 mg/d, with greater improvements occurring at the 3 and 5 mg/d levels of pST. The improvement in F/G and the greater magnitude of response observed in pigs fed 16% CP diets compared to the response of pigs fed the 13% CP diet indicate that both the performance and carcass characteristics of pigs injected with pST are dependent on the dietary CP content.; Swine Day, Manhattan, KS, November 16, 1989
Keywords: Swine day; 1989; Kansas Agricultural Experiment Station contribution; no. 90-163-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 581; Swine; Porcine somatotropin; Finishing pigs; Crude protein